jogcr 2019
DOI: 10.30699/jogcr.4.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Massive Postpartum Hemorrhage Following an Inner Myometrial Laceration: A Case Report

Abstract: Background & Objective: Postpartum hemorrhage has different etiologies. One of the rare causes is inner myometrial laceration that makes the diagnosis more difficult. This report aimed to introduce a case of massive postpartum hemorrhage following an inner myometrial laceration. Case Report: A 24-year-old primigravid woman referred to an academic Hospital due to hypertension of 140/90 and diagnosis of preeclampsia. Her pregnancy was terminated at 39 th gestational week. She received two doses of 25 μg misopros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Fisher's exact test showed that the relationship between fibrinogen levels at the end of surgery was significantly associated with the occurrence of PPH and sPPH (P=0.000). 1 -postpartum hemorrhage, 2 -severe postpartum hemorrhage, 3 -hemoglobin, 4 -platelet, 5 -prothrombin time, 6 -Partial Thromboplastin Time…”
Section: Resultsmentioning
confidence: 99%
“…Fisher's exact test showed that the relationship between fibrinogen levels at the end of surgery was significantly associated with the occurrence of PPH and sPPH (P=0.000). 1 -postpartum hemorrhage, 2 -severe postpartum hemorrhage, 3 -hemoglobin, 4 -platelet, 5 -prothrombin time, 6 -Partial Thromboplastin Time…”
Section: Resultsmentioning
confidence: 99%
“…Since its first description, there has been 16 cases of IML reported including one that was associated with secondary PPH, 7 days after delivery. 5,[7][8][9][10][11][12] In this review, only IML cases causing primary PPH are included and presented in Tables 1 and 2. The incidence of IML is not known and it is thought that some of the cases could have been missed as the diagnosis can only be made by direct examination of hysterectomized uteri or during hysterotomy. There might also be minor lacerations that had been successfully managed with intrauterine tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…Since its first description, there has been 16 cases of IML reported including one that was associated with secondary PPH, 7 days after delivery 5,7–12 . In this review, only IML cases causing primary PPH are included and presented in Tables 1 and 2.…”
Section: Discussionmentioning
confidence: 99%